Linear Equations

Can you please help solve this equation using the substitution method? I have tried and keep getting that X and Y = 7/2, but the answer in the book states no solution, inconsistent system. What am I doing wrong? Please help! Solve the systems of equations by the substitution method.
y-x=4
x-y=3
Thank you!

  1. 👍 0
  2. 👎 0
  3. 👁 122
asked by Mia
  1. Here is why there is no solution ...

    multiply the first equation by -1
    x - y = -4
    subtract the second equation ...
    0 = -7 >>>> CONTRADICTION! So, no solution.

    OR
    by substitution,
    first equation: y = x+4
    sub into second
    x-y = 3
    x - (x+4) = 3
    x-x-4=3
    0 = 7, same result.

    Your answer of x = y = 7/2 does not work in either equation.

    1. 👍 0
    2. 👎 0
    posted by Reiny
  2. Solve the following system of equations by the substitution method.

    8x = 2y + 5
    3x = y + 7

    1. 👍 0
    2. 👎 0
    posted by megan
  3. Y-X=4...(EQN 1)
    X-Y=3...(EQN 2)
    MAKING X THE SUBJECT IN EQN 2
    X=3+Y
    SUBSTITUTING IN EQN 1
    Y-(3+Y)=4
    Y-3-Y=4
    THE Y GETS ELIMINATED,HENCE THERE IS NO SOLUTION

    1. 👍 0
    2. 👎 0
    posted by jessica
  4. x=4,y=0

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

    asked by Svetlana on October 17, 2006
  2. Algebra PLEASE HELP!!

    What advantages does the method of substitution have over graphing for solving systems of equations? Choose the correct answer below. A. Graphing cannot be used to solve dependent or inconsistent systems due to the nature of the

    asked by zwgz123 on December 15, 2017
  3. Math

    I need help,my example: The sales representative say there are two floor plans available 56 total houses. Use x for floor plan 1 and y for floor plan 2 then write an equation that illistrates the situation. So I thought x+y=56,

    asked by dee on November 27, 2009
  4. ALGEBRA 1!PLZ HELP!

    Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back

    asked by SANDRO! on November 6, 2006
  5. math ALGEBRA

    Solve by either the substitution method or the addition or subtraction method 2m=n-3 3m=2n-9 Just replace n with (2m + 3) in the second equation. Then solve for m. Once you know the value of m, use either of your equations, such

    asked by DANIELLE on December 21, 2006
  6. Algebra 1

    bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were

    asked by slomo on January 3, 2015
  7. Algebra 1 HELP PLZ!!!

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 PLz HELP!! I'M NOT BOB BUT I CAN HELP ITS REALLY SIMPLE ALGEBRA X + Y = -4......EQN 1 X - Y = 2.....EQN 2 From EQN 2, let x = 2 + y Substitute that

    asked by Margie on November 2, 2006
  8. Math

    Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31 x + 3y + 2z = -21 ______________________ The answer I got for this is ( -26, 6,67) but I know its wrong and I don't know why. Help please >< my work is at

    asked by Linda on November 1, 2011
  9. Algebra 2

    If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17

    asked by Mike on April 25, 2011
  10. algebra 2

    If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + y = 2 3x + 2y = 9

    asked by mel on August 16, 2012

More Similar Questions